Zonulin Upregulation Is Associated With Increased Gut Permeability in Subjects With Type 1 Diabetes and Their Relatives - Sapone, Anna; de Magistris, Laura; Pietzak, Michelle; Clemente, Maria G.; Tripathi, Amit; Cucca, Francesco; Lampis, Rosanna; Kryszak, Deborah; Cartenì, Maria; Generoso, Maddalena; Iafusco, Dario; Prisco, Francesco; et al. (Diabetes (New York, N.Y.), 2006)
Zonulin Upregulation Is Associated With Increased Gut Permeability in Subjects With Type 1 Diabetes and Their Relatives Anna Sapone 1 2 , Laura de Magistris 2 , Michelle Pietzak 3 , Maria G. Clemente 1 , Amit Tripathi 1 , Francesco Cucca 4 , Rosanna Lampis 4 , Deborah Kryszak 1 , Maria Cartenì 2 , Maddalena Generoso 2 , Dario Iafusco 2 , Francesco Prisco 2 , Francesca Laghi 2 , Gabriele Riegler 2 , Romano Carratu 2 , Debra Counts 5 and Alessio Fasano 1 1 Mucosal Biology Research Center, University of Maryland School of Medicine, Baltimore, Maryland 2 Department Magrassi-Lanzara, Gastroenterology Unit, II University of Naples, Naples, Italy 3 University of Southern California Keck School of Medicine and the Division of Gastroenterology and Nutrition, Children’s Hospital Los Angeles, Los Angeles, California 4 Department of Biomedical Science and Biotechnology, University of Cagliari, Cagliari, Italy 5 Division of Pediatric Endocrinology, Department of Pediatrics, University of Maryland School of Medicine, Baltimore, Maryland Address correspondence and reprint requests to Alessio Fasano, MD, Mucosal Biology Research Center, University of Maryland School of Medicine, 20 Penn St., Room 345, Baltimore, MD 21201. E-mail: afasanoatmbrc.umaryland.edu Abstract Zonulin, a protein that modulates intestinal permeability, is upregulated in several autoimmune diseases and is involved in the pathogenesis of autoimmune diabetes in the BB/Wor animal model of the disease. To verify the association between serum zonulin levels and in vivo intestinal permeability in patients with type 1 diabetes, both parameters were investigated in different stages of the autoimmune process. Forty-two percent (141 of 339) of the patients had abnormal serum zonulin levels, as compared with age-matched control subjects. The increased zonulin levels correlated with increased intestinal permeability in vivo and changes in claudin-1, claudin-2, and myosin IXB genes expression, while no changes were detected in ZO1 and occludin genes expression. When tested in serum samples collected during the pre–type 1 diabetes phase, elevated serum zonulin was detected in 70% of subjects and preceded by 3.5 ± 0.9 years the onset of the disease in those patients who went on to develop type 1 diabetes. Combined, these results suggest that zonulin upregulation is associated with increased intestinal permeability in a subgroup of type 1 diabetic patients. Zonulin upregulation seems to precede the onset of the disease, providing a possible link between increased intestinal permeability, environmental exposure to non–self antigens, and the development of autoimmunity in genetically susceptible individuals. ELISA, enzyme-linked immunosorbent assay GALT, gut-associated lymphoid tissue ICA, islet cell antibody IA-2, insulinoma-associated protein 2 LA/MA, lactulose/mannitol MAdCAM-1, mucosal vascular addressin cell adhesion molecule 1 TBS-T, Tris-buffered saline 0.05% Tween 20 TJ, tight junction Footnotes The costs of publication of this article were defrayed in part by the payment of page charges. This article must therefore be hereby marked “advertisement” in accordance with 18 U.S.C. Section 1734 solely to indicate this fact. Accepted February 13, 2006. Received December 8, 2005. DIABETES